Influence of surfactant on sol-gel-prepared TiO2: characterization and photocatalytic dye degradation in water - Mkhohlakali, Andile; Jen, Tien-Chien; Ledwaba, Kabelo; Mapukata, Sivuyisiwe; Mabowa, Happy Mothepane; Letsoalo, Mokgehle R.; Ntsasa, Napo; Tshilongo, James (Frontiers in Chemical Engineering, 2024)
Titanium dioxide (TiO2) nano-powder was prepared using a sol-gel process with and without surfactant. A typical nonionic surfactant (Triton X-100) was used during the process. The phase compositions of TiO2 and surfactant-assisted TiO2 (TiO2-sa) were investigated by FTIR, X-ray diffraction (XRD) and scanning electron microscope-energy dispersive spectroscopy (SEM-EDS), and thermogravimetric analysis (TGA). Brunauer-Emmett-Teller (BET) was used to determine the nanopowder's specific surface area and pore size distribution. Moreover, transmission electron microscopy (TEM) and Selected Area Electron Diffraction (SAED) analysis exhibited particle size in the range of 65-85 nm and polycrystalline phase, respectively. UV-vis spectrophotometer showed high absorption dominating the visible region (438-450 nm) with relative redshift and reduced bandgap from 2.98 to 3.12 eV upon adding surfactant on TiO2. X-ray fluorescence spectroscopy (XRF) exhibits high purity TiO2 with more than 82% composition with the lowest relative standard deviation (RSD %). Moreover, the photoluminescence (PL) of TiO2-sa showed enhanced oxygen vacancies and surface defects which reduce the direct electron-photon (e/h+) pair recombination. TiO2-sa illustrated promising characteristic features of an active photocatalyst for the degradation of dye pollutants.